Contested Sacredness: The Struggle for Bears Ears - Keegan, Brennan (Journal of the American Academy of Religion, 2022)
Southern Utah and the Four Corners region is home to five Tribal nations, united by shared experiences of settler colonialism and a tie to the landscapes of Bears Ears National Monument. After years of Tribal advocacy to protect the site, President Obama designated the monument under the Antiquities Act in December 2016. A year later, President Trump reduced the 1.35-million-acre national monument by 85 percent to make way for uranium mining, officially sanctifying state control and natural resource extraction. Protests and lawsuits ensued. The legal status of Bears Ears continues to be contested. Religious freedom, capitalism, nationalism, environmental protection, and tourism have coalesced at the site in an example of the production, shift, and conflict of spatial relations. By mapping the constellation of spaces produced by the stakeholders, this article argues that a spatial lens points to moments of overlap and resolution as the case moves forward.